Mapping glioma heterogeneity using multiparametric 18F-choline PET/MRI in childhood and teenage-young adults. Issue 1 (16th November 2022) - Ferrazzoli, Valentina; Shankar, Ananth; Cockle, Julia V.; Tang, Christine; Al-Khayfawee, Ahmed; Bomanji, Jamshed; Fraioli, Francesco; Hyare, Harpreet
Abstract : Objective: The heterogeneity of post-treatment imaging remains a significant challenge in children and teenagers/young adults (TYA) diagnosed with glioma. The aim of this study was to evaluate the utility of 18 F-choline PET/MRI in determining intratumoural heterogeneity in paediatric and TYA gliomas. Methods: Twenty-six patients (mean age 16 years, range 8–22 years) with suspected glioma disease progression were evaluated with 18 F-choline PET/MRI. Relative cerebral blood volume (rCBV), apparent diffusion coefficient (ADC) and maximum standardised uptake values (SUVmax ) in enhancing (enh) and non-enhancing (ne) tumour volumes and normal-appearing white matter (wm) were calculated (rCBVenh, rCBVne, rCBVwm, ADCenh, ADCne, ADCwm, SUVenh, SUVne and SUVwm ). Results: Significantly higher SUVenh and SUVne compared with SUVwm were observed [SUVenh 0.89 (0.23–1.90), SUVne 0.36 (0.16–0.78) versus SUVwm 0.15 (0.04–1.19); P < 0.001 and P = 0.004, respectively]. Equivalent results were observed for ADV and rCBV (ADCenh, ADCne : P < 0.001 versus ADCwm ; rCBVenh, rCBVne : P < 0.001 versus rCBVwm ). The highest values for mean SUVmax [0.89 (0.23–1.90)] and mean rCBV [2.1 (0.74–5.08)] were in the enhancing component, while the highest values for ADC [1780 mm 2 /s (863–2811)] were in the necrotic component. Conclusion: 18 F-choline PET/MRI is able map imaging heterogeneity in paediatric and TYA gliomas, detecting post-treatment enhancing, non-enhancing, and necrotic tumour components equivalent to ADC and DSC-derived rCBV. This offers potential in the response assessment of diffuse non-enhancing gliomas and in selected cases such as posterior fossa tumours where quantitative MRI is technically difficult.